The effect of academic achievement on aggression and violent behavior: A meta-analysis. (November 2017) - Savage, Joanne; Ferguson, Christopher J.; Flores, Lesli
Highlights: Meta-analysis of studies examining the association between academic achievement and violent behavior Low academic achievement is consistently associated with violent offending Low academic achievement is associated with violent offending, controlling for nonviolent antisocial behavior Findings support the differential etiology of violence hypothesis